2015
DOI: 10.1166/jnn.2015.8328
|View full text |Cite
|
Sign up to set email alerts
|

Isomerization of Higher Alkane Over Platinum Supported on Nanoporous Materials

Abstract: The objective of this study is to evaluate the catalytic potential of Pt/MMZ-FER catalysts in hydroisomerization of long chain hydrocarbon. MMZ-FER, a nanoporous material produced from commercial ferrierite, was used as a support for the catalysts. The catalysts were characterized via X-ray powder diffraction, N2 adsorption, pyridine-IR, and the temperature-programmed desorption of ammonia. Hydroisomerization of n-dodecane was performed on Pt/MMZ-FER catalysts. Hydroisomerization requires platinum loading on M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Results showed that the protein-corona inhibits the cellular uptake of ferroferric oxide NPs, the progress may result from the surface energy change of nanoparticles with protein-corona. Although nanomaterials have been widely investigated in last two decades, [30][31][32][33][34][35][36][37][38][39][40][41][42] the findings in our work will contribute to the nanotoxicity evaluation of ferroferric oxide NPs and help to perfect their biomedical applications. …”
Section: Discussionmentioning
confidence: 99%
“…Results showed that the protein-corona inhibits the cellular uptake of ferroferric oxide NPs, the progress may result from the surface energy change of nanoparticles with protein-corona. Although nanomaterials have been widely investigated in last two decades, [30][31][32][33][34][35][36][37][38][39][40][41][42] the findings in our work will contribute to the nanotoxicity evaluation of ferroferric oxide NPs and help to perfect their biomedical applications. …”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Molybdenum oxide was grafted over SiMCM-41 via the modified ALD method. 6,12 SiMCM-41 powder was suspended in toluene and heated under reflux for 4 h in bubbling N 2 .…”
Section: Methodsmentioning
confidence: 99%
“…SiMCM‐41 was synthesized using the method described elsewhere . Molybdenum oxide was grafted over SiMCM‐41 via the modified ALD method .…”
Section: Methodsmentioning
confidence: 99%
“…This reaction transforms linear alkanes into branched ones, which have higher octane numbers and therefore utilize light gasoline fraction of atmosphere refining [1][2][3][4][5][6]. Usually, branched paraffins are obtained by isomerization over bifunctional catalysts, which have Broensted and Lewis acidic and hydrogenating-dehydrogenating active sites [7][8][9][10][11]. Mordenite zeolite and alumina are used in the role of acidic support, whereas hydrogenating-dehydrogeneting sites are usually formed by platinum group metals.…”
Section: Introductionmentioning
confidence: 99%